ASSESSMENT OF BOVINE SEMEN QUALITY BY RESAZURIN REDUCTION TEST - kumar, Umesh; Patil, Prasana; Gawande, AP (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted to assess the semen quality using Resazurin Reduction Test (RRT) in Jersey and Jersey cross bulls. A total 36 fresh ejaculates were collected for evaluation RRT, sperm motility, acrosomal integrity and sperm concentration. The mean value of RRT in bulls was 15.77±0.85 minutes.Statistical analysis revealed that RRT was highly significantly (p<0.01) and positively correlated with sperm concentration (r=0.769), sperm motility(r=0.858) and acrosomal integrity (r=0.515), hence it may be helpful in evaluating the quality of semen in bulls.